PENGARUH AGRESIVITAS PAJAK TERHADAP COST OF DEBT - Dewi Kusuma Wardani; Siti Hamzia Ahmad (Bajang Institute, 2022)
This study aims to test whether tax aggressiveness has an effect on the cost of debt. Analysis of the data used using quantitative methods and the data used are secondary data obtained from the Indonesia Stock Exchange (IDX) in 2017-2020. The number of manufacturing companies that were sampled were 46 companies with 184 company annual reports. Sampling in this study using purposive sampling method. In this study the Effective Tax Rate (ETR) is used as a measure of tax aggressiveness. This study shows that firm size has a positive effect on the cost of debt. The novelty in this study lies in the year of observation, namely from 2017-2020.